PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN SISWA MELALUI PENERAPAN METODE STRUKTURAL ANALITIK SINTETIK (SAS) BAGI ANAK BERKESULITAN MEMBACA DI KELAS II UPTD SD INPRES RSS OESAPA KOTA KUPANG. - Asbanu, Anirwati; Koroh, Taty R.; Sampe, Markus (SINERGI : Jurnal Riset Ilmiah, 2025)
The results of research by Anirwati Asbanu, Nim 200114008 with the title "Improving students' initial reading skills through the application of the Synthetic Structural Analytical (SAS) method for children with reading difficulties in class 2 UPTD SD Inpres RSS Oesapa, Kupang City." The problem of this research is whether the application of the Synthetic Structural Analytical (SAS) method can improve the beginning reading ability of grade 2 students at UPTD SD Inpres RSS Oesapa? "The aim of this research is to improve the beginning reading skills of grade 2 students at UPTD SD Inpres RSS Oesapa through the application of the Synthetic Structural Analytical (SAS) method." This type of research uses classroom action research (PTK) through several stages, namely: Planning, Implementation, Observation and Reflection. The subjects of this research were 30 students of class IIC UPTD SD Inpres RSS Oesapa, Kupang City. Data collection was carried out using observation, test and documentation techniques. The research results showed that of the 30 students who completed cycle I, there were 13 students (43.33%) because they were able to read well, while 17 students (56.77%) did not complete because they still needed guidance in initial reading. Furthermore, in cycle II of the 30 students, 26 students (86.66%) completed it because they had read well, while 4 students (13.33%) did not complete it because they still needed guidance. The results of the research showed that the application of the Synthetic Structural Analytical (SAS) method ) can improve students' initial reading abilities